Professor Vasily Ivanovich Kolesov (1904–1992) (on the 120th anniversary of his birth) - S. F. Bagnenko; G. G. Khubulava; A. A. Kurygin; V. V. Semenov; A. S. Nemkov (Вестник хирургии имени И.И. Грекова)
An outstanding surgeon and scientist, a talented teacher, one of the pioneers of world cardiac surgery, Honored Scientist of the RSFSR (1964), laureate of the USSR State Prize (1988), Colonel of the Medical Service, Doctor of Medical  Sciences, Professor Vasily Ivanovich Kolesov was born on September 24, 1904 in the village Martyanovskaya (now Ust-Kubinsky district) Vologda province. In 1931, he graduated from the 2nd Leningrad Medical Institute and worked as a therapist in the village of Chusovoy, Perm Region. From 1934 to 1938, he taught at the Department of Faculty Surgery of the Perm Medical Institute, where he prepared his Ph.D. thesis, which he defended at the Leningrad State Institute for Advanced Medical Training in 1938 and moved to Leningrad. In 1953–1955, V. I. Kolesov headed the Department of General Surgery, and in 1955–1976 – Department and Clinic of Faculty Surgery of the 1st Leningrad Medical Institute named after Academician I. P. Pavlov. On February 25, 1964, for the first time in the world, Vasily Ivanovich sewed the distal end of the transected mammary artery into the end of the circumflex artery of the heart in a seriously ill man without coronary artery perfusion. At the end of the 1960s, V. I. Kolesov began performing anastomoses using  the ASC-4 vascular stapling device, as well as devices designed by his son, E. V. Kolesov (ASC-UV and ASC-VAK), which significantly reduced the time of formation of a vascular anastomosis on a beating heart. On February 5, 1968, V. I. Kolesov for the first time operated on a patient 7 hours after her ECG registered myocardial infarction, and on May 17 of the same year, he restored the blood supply to the heart of a patient with unstable angina, proving for the first  time in the world the possibility of surgically preventing the development of myocardial infarction. V. I. Kolesov published about 200 scientific papers, including 8 monographs on general, thoracic and cardiac surgery. Vasily Ivanovich and Evgeny Vasilyevich Kolesov were the authors of more than ten global and domestic priorities. V. I. Kolesov was awarded two Orders of the Patriotic War, I and II degrees, the Order of the Red Banner of Labor, medals «For the Defense of Leningrad», «For Military Merit», «For Victory over Germany», as well as many honorary insignia. Professor Vasily Ivanovich Kolesov died on August 2, 1992 and was buried at the Bogoslovskoye cemetery in Saint Petersburg.